Effects of Linolenic Acid supplementation on Seminal Attributes of Labrador during in-vitro Storage at 4°C - Mavi, Gurjot Kaur; Singh, Ashwani Kumar (The Indian Journal of Animal Reproduction, 2022)
The purpose of this study was to evaluate the probable effects of the linolenic acid addition in different levels to the Tris based egg yolk plasma (T-EYP) extender in Labrador dog semen on spermatozoa quality during storage of semen at 4°C for 0, 24,48 and 72 hours. The collected semen from all dogs was mixed together and diluted with T-EYP. The diluted pooled semen was divided into 5 treatments (T). T1 was a control group without any linolenic acid addition. For T2 to T5 groups 0.5 ng/ml , 1.5 ng/ml, 2.5 ng/ml and 3.5 ng/ml linolenic acid were added respectively. Treatments were evaluated for sperm motility, sperm viability, morphological defect, acrosome integrity and membrane integrity after 0, 24, 48 and 72 hours of incubation at 4°C. The evaluations of spermatozoa immediately after semen collection, were revealed no significant differences among values of treatment groups, whereas after incubating the treatments for different spans of time, the sperm progressive motility and viability rates for groups supplemented with linolenic acid were significantly (P
Keywords: Chilled Semen; Linolenic Acid; Sperm Attributes; Labrador Dog Semen